Expression Profile of Multidrug Resistance Efflux Pumps During Intracellular Life of Adherent-Invasive Escherichia coli Strain LF82 - Fanelli, Giulia; Pasqua, Martina; Colonna, Bianca; Prosseda, Gianni; Grossi, Milena (Frontiers in Microbiology, 2020)
Efflux pumps (EPs) are present in all living cells and represent a large and important group of transmembrane proteins involved in transport processes. In bacteria, multidrug resistance efflux pumps (MDR EPs) confer resistance to antibiotics at different levels and are deeply implicated in the fast and dramatic emergence of antibiotic resistance. Recently, several reports have outlined the great versatility of MDR EPs in exporting a large variety of compounds other than antibiotics, thus promoting bacterial adaptation to a wide range of habitats. In several bacterial pathogens, MDR EPs contribute to increase the virulence potential and are directly involved in the crosstalk with host cells. In this work, we have investigated the possible role of MDR EPs in the infectious process of the adherent-invasive Escherichia coli (AIEC), a group of pathogenic E. coli that colonize the ileal mucosa of Crohn disease (CD) patients causing a strong intestinal inflammation. The results we have obtained indicate that, with the exception of mdtM, all MDR-EPs encoding genes present in E.coli K12 are conserved in the AIEC prototype strain LF82. The analysis of MDR EP expression during LF82 infection of macrophages and epithelial cells reveals that their transcription is highly modulated during the bacterial intracellular life. Notably, some EP genes are regulated in a cell-type specific manner, strongly suggesting that their function is required for LF82 successful infection. AIEC are able to adhere to and invade intestinal epithelial cells and, importantly, to survive and multiply within macrophages. Thus, we further investigated the role of EPs specifically induced by macrophage environment. We present evidence indicating that deletion of mdtEF genes, encoding an MDR EP belonging to the resistance nodulation division (RND) family, significantly impairs survival of LF82 in macrophages and that the wild type phenotype can be restored by trans-complementation with functional MdtEF pump. Altogether, our results indicate a strong involvement of MDR EPs in host pathogen interaction also in AIEC and highlight the contribution of MdtEF to the fitness of LF82 in the macrophage environment.